2019
DOI: 10.1186/s12920-019-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-374a, -4680, and -133b suppress cell proliferation through the regulation of genes associated with human cleft palate in cultured human palate cells

Abstract: Background Cleft palate (CP) is the second most common congenital birth defect; however, the relationship between CP-associated genes and epigenetic regulation remains largely unknown. In this study, we investigated the contribution of microRNAs (miRNAs) to cell proliferation and regulation of genes involved in CP development. Methods In order to identify all genes for which mutations or association/linkage have been found in individuals with CP, we conducted a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Ding et al (2013) used the zebrafish larval model to identify miR‐133b as a miRNA whose overexpression resulted in midfacial cleft (Ding et al, 2016). These findings were corroborated by Suzuki et al (2019) using human PMCs (Suzuki, Li, et al, 2019). Among the validated target genes of miR‐133b in human cells were key regulators of palatogenesis, including an Fgf signaling receptor FGFR1 and the transcription factor PAX7 .…”
Section: Micrornas and Orofacial Cleftssupporting
confidence: 68%
See 1 more Smart Citation
“…Ding et al (2013) used the zebrafish larval model to identify miR‐133b as a miRNA whose overexpression resulted in midfacial cleft (Ding et al, 2016). These findings were corroborated by Suzuki et al (2019) using human PMCs (Suzuki, Li, et al, 2019). Among the validated target genes of miR‐133b in human cells were key regulators of palatogenesis, including an Fgf signaling receptor FGFR1 and the transcription factor PAX7 .…”
Section: Micrornas and Orofacial Cleftssupporting
confidence: 68%
“…Two recent studies leveraged the literature and in silico modeling to identify miRNAs associated with OFCs and subsequently validate predicted target genes in cultured human cells. Suzuki et al (2019) identified miR‐133b, miR‐374a‐5p, and miR‐4680‐3p as being differentially regulated in CPO patients (Suzuki, Li, et al, 2019). The latter two miRNAs were validated to target WNT5A expression using miRNA mimics in human PMCs.…”
Section: Micrornas and Orofacial Cleftsmentioning
confidence: 99%
“…A total of 177 gene mutations has been reported in cases of CL/P in humans, 13,14 and a total of 252 genes has been identified in genetically mutated mouse models exhibiting CP 28 . Among them, 49 genes ( Alx1 , Alx3 , Bmp4 , Chd7 , Col2a1 , Col11a1 , Dhcr7 , Efnb1 , Eya1 , Fgf8 , Fgf10 , Fgfr1 , Fgfr2 , Flna, Foxc2 , Foxe1 , Gli2 , Gli3 , Grhl3 , Hic1 , Irf6 , Jag2 , Kcnj2 , Msx1 , Ofd1 , Pax9 , Pdgfc , Prickle1 , Ptch1 , Recql4 , Ror2 , Satb2 , Six3 , Ski , Sox9 , Sox11 , Sumo1 , Tbx1 , Tbx22 , Tcof1 , Tfap2a , Tgfb3, Tgfbr1 , Tgfbr2 , Trp63 , Twist1 , Vax1 , Wnt5a , and Zeb2 ) are common between humans and mice (Table 3).…”
Section: Pathological Mechanisms Of Cleft Palatementioning
confidence: 99%
“…[8][9][10][11] Approximately 70% of CL/P is non-syndromic, but more than 487 syndromes in which CL/P is a part of the clinical features have been reported. [12][13][14] Asian and Native American populations have the highest prevalence, as high as 1 in 500, and African populations have the lowest prevalence, at approximately 1 in 2500. The occurrence of CL/P also differs by gender and laterality.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation